PERAN ORANG TUA DALAM MOTIVASI BELAJAR ANAK DI KELAS IV SD NEGERI 004 PELALAWAN - Miranda Miranda; Siti Quratul ‘Ain (STKIP Subang, 2022)
This study aims to find out how the role of parents in students' learning motivation in grade IV SD Negeri 004 Pelalawan and to find out whether parents' barriers to student motivation in grade IV SD Negeri 004 Pelalawan. This type of qualitative research uses data collection techniques, namely observation, interviews and documentation. The technique of checking the validity of the data in the study was carried out by triangulation of techniques, sources, and time. The source of this research is the parents of fourth grade students at SD Negeri 004 Pelalawan. The results of this study indicate that parents play a role in motivating students' learning in class IV SD Negeri 004 Pelalawan with all the difficulties that do not prevent parents from giving the best for their children, including parents play a role in students as educators, motivators, facilitators and mentors. The obstacles that researchers can encounter in the field are limitations on the lack of knowledge from parents and the difficulty of the parents' economy to meet all student learning facilities.